How the Spread of User-Generated Contents (UGC) Shapes International Tourism Distribution: Using Agent-Based Modeling to Inform Strategic UGC Marketing. (September 2021) - Zhang, Ye; Gao, Jie; Cole, Shu; Ricci, Peter
While user-generated contents (UGC) are recognized as increasingly important to destination marketing, many DMOs are uncertain how to strategically manage them to their best advantage, largely due to their lack of understanding of mechanisms underlying the UGC effects. By integrating multiple theories of travel decision-making and UGC distribution, this study develops and validates an agent-based model to inform DMOs of potential causal mechanisms of how individual tourists' UGC behavioral features shape international arrival distribution via the social media channels of review sites (RSs) and social networking sites (SNSs). Simulated experiments with the model decompose and assess the complex UGC behavioral effects, which further suggest context-based favorable UGC distribution statuses for DMOs' strategic UGC marketing. The model developed following a rigid procedure offers a promising UGC research approach toward the combination of restrictive causal conceptualization and real-life replicability. It also provides an adaptive prototype for cost-effective UGC effect assessments by DMOs.